2019
DOI: 10.1101/655555
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Atoh8 acts as a regulator of chondrocyte proliferation and differentiation in endochondral bones

Abstract: 24 Atonal homolog 8 (Atoh8) is a transcription factor of the basic helix-loop-helix (bHLH) protein 25 family, which is expressed in the cartilaginous elements of endochondral bones. To analyze 26 its function during chondrogenesis we deleted Atoh8 in mice using a chondrocyte-27 (Atoh8 flox/flox ;Col2a1-Cre) and a germline-(Atoh8 flox/flox ;Prx1-Cre female ) specific Cre allele. In 28 both strains, Atoh8 deletion leads to a reduced skeletal size of the axial and appendicular 29 bones, but the stages of phenotyp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 54 publications
2
5
0
Order By: Relevance
“…However, no signals were observed in osteoblasts ( Fig. 2a, b, asterisks), and prehypertrophic chondrocytes exhibited substantial signal spots of Atoh8, as reported previously 34 (Fig. 2b, arrowhead).…”
Section: Atoh8 Is Expressed In Osteoblasts In Adult Bonesupporting
confidence: 86%
See 4 more Smart Citations
“…However, no signals were observed in osteoblasts ( Fig. 2a, b, asterisks), and prehypertrophic chondrocytes exhibited substantial signal spots of Atoh8, as reported previously 34 (Fig. 2b, arrowhead).…”
Section: Atoh8 Is Expressed In Osteoblasts In Adult Bonesupporting
confidence: 86%
“…33,34,[44][45][46] These Atoh8-KO mice are viable and healthy and obtained at the expected Mendelian ratio. 33,34,45,46 However, there is no report on the bone phenotype of adult Atoh8-deficient mice. In this study, we found ubiquitous expression of Atoh8 in tissues from adult mice, with high levels in the lung, stomach, liver, spleen, and skin (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations